Food Composition and Dedicated Databases: Key Tools for Human Health and Public Nutrition - Durazzo, Alessandra; Lucarini, Massimo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue collects research on and applications of the relationship between food, nutrition, and databases. The development of databases of nutrients, bioactive compounds, and metabolites are key tools for human health and public nutrition and represent resources for a wide range of applications in food, pharmaceutical, nutraceutical, epidemiology, and medicinal areas. The current research trends are highlighted.